Proposition of a structured list of information items to be transmitted to primary caregivers after in-hospital medication optimization: a qualitative study. Issue 3 (4th May 2021) - Visade, Fabien; Lefebvre, Antoine; Floret, Emmanuel; Decaudin, Bertrand; Puisieux, François; Delecluse, Céline; Beuscart, Jean-Baptiste
ABSTRACT: Background and objective : Defective transmission of drug information during the transition from hospital to home care are causes of adverse drug reactions in older patients. We aimed to reach a consensus concerning information about changes in treatment to be transmitted to primary caregivers when an older patient is discharged from hospital. Methods : A qualitative focus group study was conducted with general practitioners, geriatricians, community pharmacists, and hospital pharmacists providing care for older patients. Four steps were used to reach a focus group consensus: 1) presentation of the purpose of the focus group; 2) generation and enumeration of ideas; 3) sharing opinions about these ideas; 4) voting to create a list of ranked items. The process involved three focus groups. Results : A consensus was reached on ten items: indication for continued, discontinued, newly introduced or changed treatments and their duration; reasons for discontinuing drugs or introducing new drugs; information about re-evaluating treatments; reasons for hospital stay, significant elements and diagnosis at discharge; administrative information concerning the patient; the name of the primary care physician, and the discharging hospital unit and the physician(s) in charge; known allergies, information about liver and kidney failure; main adverse effects to monitor; date of latest blood tests; hospital admission/discharge dates. Conclusion : The consensus on the list of information items concerning changes in the treatment should be used by hospital physicians and pharmacists to ensure safe patient discharge.